Measuring the impact of business: Sustainability Reporting by Corporations in Emerging Asia - Leonardo L. Sta. Romana (ZBW – Leibniz Information Centre for Economics, 2018)
This study addresses the issue of sustainability reporting by corporations, and the framework(s) and guidelines used in the preparation of those annual reports. It takes as its starting point the UN Sustainable Development Goal 12: "Ensure sustainable consumption and production patterns", with its Target 12.6: "Encourage companies, especially large and transnational companies, to adopt sustainable practices and to integrate sustainability information into their reporting cycle". And it is the Indicator 12.6.1: "Number of companies publishing sustainability reports" that provides the inspiration for the idea for doing this study. The study provides, firstly, a brief background on the group responsible for the sustainability reporting framework widely used by companies, the Global Reporting Initiative (GRI). This is followed with another short background on a second, though newer, group with another framework, the International Integrated Reporting Council (IIRC). The study presents - to the best of the author's knowledge - the first comparative study of corporate sustainability reports (and the frameworks used) across ten Emerging Asian economies. It proceeds to this core empirical contribution of the paper by explaining the process how the corporations in Emerging Asia were selected for inclusion in the study. It notes that the companies and the economies of origin were not picked directly for inclusion. The first step was to find reputable corporate sustainability rankings and ratings. Seven information sources yielded a list of 150 companies from ten Emerging Asian economies. These economies are: China, Hong Kong, India, South Korea, Taiwan, Thailand, Indonesia, Malaysia, Philippines and Singapore. It then presents the findings from a survey of the sustainability reports of the 150 corporations. Across the entire sample, almost 90 percent cite the use of the GRI guidelines. In three economies with more than just a handful of companies in the sample – South Korea, Taiwan and Thailand – all of their companies cite the GRI framework. However, the picture is not as one-sided in India, where less than half cite the GRI.
Additional information: This paper was written in response to a call for papers on “Measuring the Impact of Business on Well-being and Sustainability” by the OECD Better Life Initiative and HEC Paris Business School/SnO (Society and Organizations) Center. An abstract, on which this paper is based, went through the evaluation process of an OECD and HEC Paris/SnO Center selection committee.
Keywords: D62; M2; O44; Q5; Q56; 330; Environmental sustainability; Corporate social responsibility (CSR); Environmental economics; Sustainable development; Sustainable development goals (SDGs); Sustainable reporting; Environment and development; Emerging Asia; Environmental; social and governance (ESG); Global Reporting Initiative (GRI); International Reporting Council (IIRC); Integrated Reporting; China; Hong Kong; India; South Korea; Taiwan; Thailand; Indonesia; Malaysia; Philippines; Singapore